Management of patients with suspected infectious diarrhoea in hospitals in England. Issue 3 (July 2015) - Buchanan, J.; Wordsworth, S.; O'Connor, L.; Pike, G.; Walker, A.S.; Wilcox, M.H.; Crook, D.W.
Summary Background Advances in molecular and genomic testing for patients with suspected infectious diarrhoea are on the horizon. It is important to understand how infection control and microbiology departments currently operate with respect to the management of these patients in order to assess the implications of more widespread diagnostic testing. However, there are few data available on current practice in this context. Aim To describe current infection control and microbiologist practice across England with respect to the management of patients with suspected infectious diarrhoea. Methods Hospitals in England completed three questionnaires on current testing practice in this context. Questionnaire design was informed by current practice within the Oxford University Hospitals group. Findings Forty-one percent of hospitals completed at least one questionnaire. A notable proportion of staff time was devoted to the management of patients with suspected infectious diarrhoea. Staff training was generally good, but compliance with policy documents was only 80%. Cleaning and isolation policies varied across hospitals, suggesting that either these were not evidence-based, or that the evidence base is weak. There was more agreement on outbreak definitions, management, and cohorting policies. Stool-testing decisions were mainly driven by patient characteristics, whereas strain typing was infrequently used (except to investigate Clostridium difficile infections). Multiple practical difficulties associated with patient management were identified, along with a clear appetite for more widespread genomic diagnostic testing. Conclusion Managing patients with suspected infectious diarrhoea is a major burden in England. Advances in testing practice in this context could have significant clinical and economic impacts.